The Ethical Aspect of the Relationship of the Individual and the State in the Libertarian Perspective of Murray N. Rothbard - Płaszczyca, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2014)
On the grounds of the libertarian ethics presented by Murray N. Rothbard, the state is an institution which acts against individuals and whole societies. The state steals money from its citizens (taxes), stands in the way of free market development and controls the economy, thus hindering entrepreneurship. Besides that, the state – through its rules and regulations – limits every man's right to make moral choices. The state is an immoral institution, therefore its citizens have the right to refuse to pay taxes, follow orders, and even – in some circumstances – corrupt civil servants. In this paper we analyse Rothbard’s ethics and look into the arguments of critics of libertarian thought. Practical social and economic solutions that emerge from Rothbard’s point of view are also considered.